Predictive factors of the attack efficacy: the case of the Brazilian women`s Volleyball League champion team - Rodrigues Rocha, A. C.; Barreiros Freire, A.; Rodrigues Martins, L.; Pereira Maia, M.; da Silva Guimaraes, J.; Ugrinowitsch, H.; de Oliveira Castro, H.; De Conti Teixeira Costa, G. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
The aim was to identify the predictive factors of the attack efficacy of the Brazilian women`s League Champion team according to the level of performance of the opposing team. The sample was composed of the observation of 1137 attacks in 21 games of the 2015-2016 Brazilian women`s Volleyball League champion team. The results were significant to identify the predictive factors of the attack efficacy against high (x2=110.562; p<0.00001), intermediate (x2=64.134; p<0.00001) and low (x2=62.137; p<0.00001) performance opponents. Thus, it is concluded that when playing against high- performance teams, powerful attack for position 6 and second attack tempo increase the chances of attack point; powerful attacks for position 1 and 5 reduce the chances of game continuation; and powerful attack for position 6 increases the chances of blocking. In addition, in games against intermediate-performance teams, reception that allows organized attack without all attack options reduces the chances of attack point and game continuation, while the reception effect did not seem to be a predictive factor of the attack efficacy in games against high- and low-performance opponents and, finally, in games against low-performance teams, powerful attack for position 1 reduces the chances of game continuation and attack blocking.